Case Report Internal Carotid Artery Dissection Presenting as Isolated Hypoglossal Nerve Palsy – A Case Report: Hypoglossal palsy in carotid dissection (Bombay Hospital Journal, 2024)
As compared to other cranial nerves, hypoglossal nerve palsy is rare; and is often associated with other lower cranial nervepalsies. The most common causes of hypoglossal nerve palsies are tumors followed by trauma, stroke, surgery, infection, andmultiple sclerosis. We report a case of a 55-year-old male presenting with dysphagia, dysarthria, and difficult mastication. Hewas diagnosed to have isolated hypoglossal nerve palsy secondary to compression by internal carotid artery dissection (ICAD).He was treated conservatively with antiplatelets and showed improvement on a 6-month follow-up. ICAD is a dangerous entitywith possible endangering complications and hence recognition of it is critical for appropriate treatment and prevention ofpossible complications. ICAD should be considered in differential diagnosis for isolated hypoglossal nerve palsy.
Keywords: Carotid dissection, Hypoglossal nerve palsy, Treatment of dissection